The optimal migration duration and activity choice after re-migration - Dustmann, Christian,Kirchkamp, Oliver (IZA, 2001)
If migrants return to their origin countries, two questions arise which are of immediate economic interest for both immigration and emigration country: What determines their optimal migration duration, and what are the activities migrants choose after a return. Little research has been devoted to these two issues. This paper utilises a unique survey data set which records activities of returned migrants. We first illustrate the activities of immigrants after returning. We show that more than half of the returning migrants are economically active after return, and most of them engage in entrepreneurial activities. We then develop a model, where migrants decide simultaneously about the optimal migration duration, and their after-return activities. Guided by this model, we specify and estimate an empirical model, where the after-return activity, and the optimal migration duration are simultaneously chosen.
Literaturverz. S. 30 - 31
Keywords: Arbeitspapier; Graue Literatur; Dauer; Rückwanderung; Berufswahl; Erwerbstätigkeit; Intertemporale Entscheidung; Lebenszyklus; Schätzung; Theorie; Deutschland; Migrationsforschung